CO04 | Direct oral anticoagulants in antiphospholipid syndrome: a single center real-life experience (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Current guidelines recommend against using Direct Oral Anticoagulants (DOACs) in patients with antiphospholipid syndrome (APS). However, there is little evidence to support these recommendations, except for triple-positive aPL profiles. Real-life studies have shown conflicting data regarding the treatment of so-called low-risk APS patients, i.e., those not triple-aPL positive. To evaluate the efficacy and safety of DOACs versus Vitamin K antagonist (VKA) in real-life APS patients and to identify risk factors predictive of the efficacy of DOACs in APS.